ABANICOS DEL MUSEO DE MURCIA - Gutiérrez García, María de los Angeles (Imafronte, 1995)
Cataloguing the contents of any museum is essential for the subsequent study and understanding of any artistic display. The aim of this paper is to classify the collection of fans in the Museum of Murcia. The origin of these exhibits is sometimes obscure, although most are donations. Almost all of them date from the 19th century, some from the 20th century. They are on display in the Archaeology Room in the Museum of Murcia and although not items of exceptional quality they nonetheless reflect the various prototypes from the 19th century.